Transcriptional regulation of the ABCC6 gene and the background of impaired function of missense disease-causing mutations - Arányi, Tamás; Bacquet, Caroline; de Boussac, Hugues; Ratajewski, Marcin; Pomozi, Viola; Fülöp, Krisztina; Brampton, Christopher N.; Pulaski, Lukasz; Le Saux, Olivier; Váradi, András (Frontiers in Genetics, 2013)
The human ABCC6 gene encodes an ABC transporter protein expressed primarily in the liver and to a lesser extent in the kidneys and the intestines. We review here the mechanisms of this restricted tissue-specific expression and the role of hepatocyte nuclear factor 4α which is responsible for the expression pattern. Detailed analyses uncovered further regulators of the expression of the gene pointing to an intronic primate-specific regulator region, an activator of the expression of the gene by binding C/EBPbeta, which interacts with other proteins acting in the proximal promoter. This regulatory network is affected by various environmental stimuli including oxidative stress and the ERK1/2 pathway. We also review here the structural and functional consequences of disease-causing missense mutations of ABCC6. A significant clustering of the missense disease-causing mutations was found at the domain-domain interfaces. This clustering means that the domain contacts are much less permissive to amino acid replacements than the rest of the protein. We summarize the experimental methods resulting in the identification of mutants with preserved transport activity but failure in intracellular targeting. These mutants are candidates for functional rescue by chemical chaperons. The results of such research can provide the basis of future allele-specific therapy of ABCC6-mediated disorders like pseudoxanthoma elasticum or the generalized arterial calcification in infancy.